ACQUISITION OF FOREIGN CITIZENSHIP BY MOLDOVAN IMMIGRANTS - TABAC, Tatiana (Economy and Sociology, 2021)
The paper explores some aspects of the acquisition of foreign citizenship by immigrants from Moldova. The purpose of the study is to estimate the size and geography of acquisition of foreign citizenship in context of migration policies changes in countries of destination. The study is based on statistical analysis of the OECD, Eurostat database and other representative sources, as well as an analysis of migration policy of the countries of citizenship acquisition. The results show that about a million people received foreign citizenship from 1992 up to present. The main countries for acquiring citizenship are: Romania, Russia, USA, Portugal, Italy, Bulgaria, Canada and Germany. The access of Moldova population to citizenship of developed countries contributes to the intensification and expansion of international migration. For Moldovan immigrants, the policies of the countries of destination have an important role in the process of acquiring citizenship.